INDICATOR SYSTEM, MONITORING WATER USE EFFICIENCY - Kholbaev B. M.; Shiryaeva M. F.; F. Erisman; A. N. Kostyakov (Web of Journals Publishing, 2024)
The articles are presented according to the established directions of assessing the effectiveness of automated control systems.
Keywords: Automated control systems, capital investments, damage minimization, water use, water users, inter-farm irrigation system